Peut-on parler d’idéologie « séparatiste » au Mexique ? A propos de la persistance des catégories indien/non indien en contexte migratoire - Françoise Lestage (Nuevo mundo - Mundos Nuevos, 2013)
In Mexico, the difference between indígena (Indian) and mestizo (other citizens = non-Indian) is set as a priori. It is not just rhetoric, but a separation which occupies a central place in the arrangement of Mexican society and its image. In this article we assume that this separation scheme is based on a separatist ideology carried by the holders of power (political, administrative, religious or scientific) in both the majority and minority. Such an ideology assumes the existence of two groups of people distinguished by various criteria (political, legal, cultural or educational) combined in systems that change over time and across regions. With the case of Mixtec migrants in Tijuana, we show that this separatist ideology continues while the material conditions of separation disappear. From local to national, in all its representations, Mexican society is thought and seen through the prism of separatism, including the methodological separatism of social scientists. It is also organized by separatist policy, inspired by the knowledge holders (religious or scholars) to "improve" the conditions of minorities.